Evaluation and Optimization of Cooling System for Generator and Bearing at Cirata Hydroelectric Power Plant - Hariyanto Hariyanto; Ary Bachtiar (IPTEK Journal of Proceedings Series, 2019)
Cirata hydroelectric is located in Purwakarta district, West Java, Indonesia. The cooling system is one of the main equipment in the hydroelectric generator that serves to cool the generator and bearing. In recent years, water quality has been a decreased in Cirata dam causing high levels of corrosion rate and abrasion of piping and heat exchanger equipment. Currently, the modification of the cooling system from open loop into closed loop at unit 1 has occurred. This study aims to optimize the closed loop cooling system in order to be able to serve all heat exchangers with better heat effectiveness and low cost. Second, it aims to evaluate the closed loop cooling system before and after optimization. The optimization analysis of the closed loop system was conducted by means of redesigning the shell and tube heat exchangers by referring to TEMA standards through tube diameter variations (1/2", 5/8" and 3/4"). These diameter variations aim to know the effect on heat transfer performance, such as the number of tubes, overall thermal transfer coefficient, total heat transfer surface area, and heat exchange cost. After obtaining the most economical design of HE (heat exchanger), the CBA evaluation of the closed loop cooling system was carried out through the NPV method. The results show that the larger used tube diameter decreases the number of tubes, while the heat transfer surface area increases as a result of the decrease in the overall heat transfer coefficient. The decreased number of tubes from 1/2" to 5/8" tube diameter is by 17.9% and the increased heat exchange production cost is by 2.18%. In case of the tube diameter increase from 5/8" to 3/4", a decrease in the number of tubes occurs by 7.9% and an increase in the heat exchange rate occurs by 4.07%. The total cost of the existing closed loop cooling system compared to the redesigned one decreases by 7.7%